2022
DOI: 10.1136/bmjopen-2021-052326
|View full text |Cite
|
Sign up to set email alerts
|

Is grip strength linked to body composition and cardiovascular risk markers in primary schoolchildren? Cross-sectional data from three African countries

Abstract: ObjectivesMuscular strength represents a specific component of health-related fitness. Hand grip strength (HGS) is used as an indicator for musculoskeletal fitness in children. HGS can also be used as a marker of cardiometabolic risk, but most available HGS data are derived from Western high-income countries. Therefore, this study examines whether HGS is associated with body composition and markers of cardiovascular risk in children from three sub-Saharan African countries.DesignCross-sectional study.SettingPu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
5
0
3
Order By: Relevance
“…Another study that measured the relationship between adiposity and muscular strength in Chilean students showed that participants with a risk of abdominal obesity had increased risk of poor relative HGS (i.e., the MQI) [ 60 ]. Likewise, another study showed that HGS is related to lower body fat in schoolchildren [ 61 ]. Improvements in HGS could also promote better HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Another study that measured the relationship between adiposity and muscular strength in Chilean students showed that participants with a risk of abdominal obesity had increased risk of poor relative HGS (i.e., the MQI) [ 60 ]. Likewise, another study showed that HGS is related to lower body fat in schoolchildren [ 61 ]. Improvements in HGS could also promote better HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Nuestros resultados son consistentes con evidencias previas que identifican a la fuerza prensil como un indicador de la composición corporal, específicamente en las variables de masa musculoesquelética y proteínas 23, 24 . Aunque la fuerza prensil evalúa directamente la fuerza máxima de la mano, es un predictor adecuado de la fuerza muscular total en niños, adolescentes, adultos y personas mayores 25 .…”
Section: Discussionunclassified
“…En concordancia con este supuesto teórico, estudios en países europeos han indicado la evaluación de la fuerza prensil como herramienta de tamizaje en las escuelas, sin embargo, en países de ingresos socioeconómicos medianos y bajos hay pocas evidencias que evalúen la fuerza prensil y su relación con la composición corporal 27 . Recientemente, un estudio multicéntrico desarrollado en países africanos encontró una asociación positiva entre la fuerza de presión y la masa muscular (β = 7,68 IC 95 %: 5,0-10,4), incluso después de controlar por variables de confusión biológicas y del entorno, indicando así una posible relación causal 24 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…All schools (quintile 3 schools) were located in peri-urban, marginalized communities. Results from this study have been published previously [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. However, the objectives articulated above have yet to be examined, and hence, the findings presented in the current publication are original.…”
Section: Methodsmentioning
confidence: 99%